Maternal and perinatal outcome of teenage deliveries in Bamako’s district - Théra, Tiounkani; Mounkoro, Niani; Téguété, Ibrahim; Kouma, Aminata; Traoré, Zouma O.; Kanté, Ibrahim; Diarra, Elizabeth (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: We initiated this study for determining the maternal and fatal outcome of deliveries among the teenage to formulate the recommendations for reducing the maternal and neonatal morbidity and mortality among the teenage. We compared maternal and foetal outcome of deliveries among the teenage to that of adult women. Methods: It was a prospective analytical case/control study running in the Bamako’s district for 6 month comparing deliveries among one population of teenage elderly of 14-19 years and another population of women of 20 to 29 years having birth in our service hang the same period of the study. Used test statistics is the chi square of Pearson. For both groups we determined Odds Ratio (OR) and its interval of confidence (IC) to 95%. Results: We recorded 350 teenagers’ deliveries among 3703 deliveries (9.4%). The pelvic was normal among 66.3% of case versus 73.5% among the controls (p >0.05). The extended labor (≥12 hours) was found among 6.6% of case versus 3.3% of controls (p >0.05). We recorded 57.3% vaginal deliveries among the case versus 46.2% among the controls (p >0.05). We recorded 3 cases of maternal death all among the controls. 71% of new-born had an Apgar score ≥7 to the first minute among the case versus 81.2% among the controls. It was no significant difference in terms of vital outcome of new-born and of small weight birth in both groups (p >0.05). Conclusions: If teenage pregnancies are benefit the adequate prenatal care, there would be any significant difference between maternal and perinatal outcome of the deliveries among the teenage and of adult's people.